Pharmacokinetics and pharmacodynamics of single and multiple doses of prasugrel in healthy native Chinese subjects - Cui Yi-min; Wang Zi-ning; Chen Xiao-wen; Zhang Hui-lin; Zhao Xia; Zhou Ying (Acta Pharmacologica Sinica; Vol 33, No 11 (November 2012): Acta Pharmacologica Sinica (Special Feature: Pharmacometrics), 2016)
Aim: To characterize the pharmacokinetics (PKs), pharmacodynamics (PDs), and tolerability of different dose regimens of prasugrel in healthy Chinese subjects. Methods: This was a single-centered, open-label, parallel-design study. Subjects received a single loading dose (LD) of prasugrel followed by once-daily maintenance dose (MD) for 10 d. They were enrolled into 3 groups: 60 mg LD/10 mg MD; 30 mg LD/7.5 mg MD; 30 mg LD/5 mg MD. Blood samples were collected after the first and last dose. The serum concentration of the active metabolite of prasugrel was determined using a LC/MS/MS method. Platelet aggregation was assessed using the VerifyNow-P2Y12 assay. Results: Thirty-six healthy native Chinese subjects (19 males) aged 18–45 were enrolled; mean age and body weight were similar across the treatment groups (n=12 for each). The metabolite AUC0–4 and Cmax increased dose-proportionally across the dose range of 5 mg to 60 mg. The median Tmax was 0.5 h in all groups. The PD parameters, indicated by the inhibition of ADP-induced platelet aggregation, were met more rapidly in the 60 mg group than the 30 mg group after the LD (94%–98%). This high degree of inhibition of platelet aggregation was maintained following the 10 mg MD (87%–90%) and was lower in the 7.5 mg and 5 mg MD groups (79%–83% and 64%–67%, respectively). Prasugrel was well tolerated in healthy Chinese subjects for single doses up to 60 mg and a MD of 10 mg for 10 d. Conclusion: The PKs and PDs of the active metabolite of prasugrel were similar to those in Chinese subjects reported by a previous bridging study, which demonstrated that the exposure to the active metabolite in Chinese subjects was higher than in Caucasians.